Discovery of a highly eccentric, chromospherically active binary: ASASSN-V J192114.84+624950.8. Issue 1 (17th May 2022) - Way, Zachary S; Jayasinghe, T; Kochanek, C S; Stanek, K Z; Vallely, Patrick; Thompson, Todd A; Holoien, Thomas W-S; Shappee, Benjamin J
ABSTRACT: As part of an All-Sky Automated Survey for SuperNovae (ASAS-SN) search for sources with large flux decrements, we discovered a transient where the quiescent, stellar source ASASSN-V J192114.84+624950.8 rapidly decreased in flux by 55 per cent (∼0.9 mag) in the g band. The Transiting Exoplanet Survey Satellite light curve revealed that the source is a highly eccentric, eclipsing binary. Fits to the light curve using phoebe find the binary orbit to have e = 0.79, P orb = 18.462 d, and i = 88.6°, and the ratios of the stellar radii and temperatures to be R 2 / R 1 = 0.71 and T e, 2 / T e, 1 = 0.82. Both stars are chromospherically active, allowing us to determine their rotational periods of P 1 = 1.52 d and P 2 = 1.79 d, respectively. A Large Binocular Telescope/Multi-Object Double Spectrograph spectrum shows that the primary is a late-G- or early-K-type dwarf. Fits to the spectral energy distribution show that the luminosities and temperatures of the two stars are L 1 = 0.48 L⊙, T_1= 5050 K, L 2 = 0.12 L⊙, and T_2 = 4190 K . We conclude that ASASSN-V J192114.84+624950.8 consists of two chromospherically active, rotational variable stars in a highly elliptical eclipsing orbit.